Stepwise development of an implementation protocol to support the prescription of Exercise = Medicine by clinicians using the Implementation Mapping approach - van Nassau, F.; Nauta, J.; Bouma, A. J.; Krops, L. A.; van den Akker- Scheek, I.; Diercks, R. L.; de Jong, J.; Leutscher, H.; Stevens, M.; van Twillert, S.; van Mechelen, W.; Zwerver, J.; et al. (Frontiers in Health Services, 2025)
IntroductionSeveral barriers, such as lack of time, knowledge and support, hinder clinicians from providing an individually tailored physical activity (PA) prescription and referral to their patients. As a result, “exercise is medicine” (E = M) is not systematically implemented in clinical care today. Many studies have identified facilitators and barriers to implementation, yet linking these factors to tailored implementation strategies is still an under-researched area. Therefore, this study aimed to apply Implementation Mapping to develop an implementation protocol to support the individually tailored PA prescription in hospital care.MethodsWe used strong stakeholder participation and, we applied the five tasks of the systematic Implementation Mapping approach to match implementation strategies to implementation barriers and facilitators identified through interviews with clinicians working at two university hospitals in the Netherlands.ResultsWe identified clinicians as primary actors. Secondary actors were managers of the departments and stakeholders in the broader context. For each actor group, performance objectives were defined. We matched previously identified facilitators and barriers to theory and evidence-informed implementation strategies from the Effective Practice and Organisation of Care taxonomy using the CFIR Strategy Matching Tool. Next, we translated these implementation strategies (e.g., active learning, audit, and feedback, technical assistance, peer education) into practical activities to support the implementation of the E = M tool, such as training for clinicians, creating overviews of possible local exercise referral options, and appointing role models for clinicians. Lastly, these activities were bundled into an implementation protocol. The implementation protocol consisted of a set of implementation activities to support and guide clinicians during the adoption, implementation, and sustainability process of the prescription of E = M. All activities were supported by implementation tools, practical applications, and materials while allowing tailoring to the specific clinical context.Discussion/conclusionThis study illustrates the application of Implementation Mapping to design an implementation protocol to support and guide the prescription of E = M by clinicians in the hospital environment, using strong stakeholder participation in the development process. The stepwise development of the implementation protocol can serve as an example for researchers or practitioners preparing for E = M implementation.